1992
DOI: 10.1002/jnr.490330202
|View full text |Cite
|
Sign up to set email alerts
|

β/A4 domain of APP: Antigenic differences between cell lines

Abstract: The expression of amyloid precursor protein (APP) in olfactory neuroblasts has been examined with a panel of antibodies directed against varied regions of the APP molecule. The pattern of reactivity was compared to that in the transformed human glial cell line SVG, human cortical brain tissue, and in kidney epithelial 293 cells containing stably transfected and overexpressed human APP751. Antibodies directed against the C-terminus and extracellular domains of amyloid precursor protein (APP) react more strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For SZ and PD these differences have been modest, perhaps because these cell types do not reflect tissue-specific differences important for brain function (Matigian et al, 2008;Wang et al, 2009). As a neural tissue, the olfactory mucosa might be more relevant, as demonstrated previously by disease-associated differences in cell functions (Wolozin et al, 1992a;Féron et al, 1999;McCurdy et al, 2006) and tissue structure (Arnold et al, 2001;Ronnett et al, 2003). ONS cells provide new patient-derived, stem-cell-based models of neurological disease that are accessible in all adults and provide new routes for understanding the pathogenesis of complex diseases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For SZ and PD these differences have been modest, perhaps because these cell types do not reflect tissue-specific differences important for brain function (Matigian et al, 2008;Wang et al, 2009). As a neural tissue, the olfactory mucosa might be more relevant, as demonstrated previously by disease-associated differences in cell functions (Wolozin et al, 1992a;Féron et al, 1999;McCurdy et al, 2006) and tissue structure (Arnold et al, 2001;Ronnett et al, 2003). ONS cells provide new patient-derived, stem-cell-based models of neurological disease that are accessible in all adults and provide new routes for understanding the pathogenesis of complex diseases.…”
Section: Discussionmentioning
confidence: 94%
“…The olfactory mucosa, the organ of smell in the nose, is a neural tissue that is accessible in human adults (Féron et al, 1998) and demonstrates disease-dependent alterations in cell biology in Alzheimer's disease, Rett syndrome, fragile X syndrome and SZ (Wolozin et al, 1992a;Abrams et al, 1999;Féron et al, 1999;Arnold et al, 2001;Ronnett et al, 2003;McCurdy et al, 2006). The olfactory sensory neurons are replaced by neurogenesis that continues throughout adult life from stem cells on the basement membrane (Mackay-Sim and Kittel, 1991;Leung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to produce large stocks and biobank ONS cells has enabled investigation of several patient and control trials, which can harness individual phenotypic differences and elucidate disease-associated variability (Mackay-Sim, 2012). ONS cells derived from patients with neurodevelopmental and neuropsychiatric disorders (Rett's syndrome (Ronnett et al, 2003), Fragile X syndrome (Abrams et al, 1999) schizophrenia, bipolar disorder (Matigian et al, 2010;McCurdy et al, 2006) and neurodegenerative diseases (Parkinson's disease (Matigian et al, 2010), AD (Wolozin et al, 1992)) display disease-specific alterations. Recent studies of ONS cells have shown that neurodevelopment-associated pathways such as the G1/S phase transition are significantly different in cells derived from schizophrenia patients (McCurdy et al, 2006).…”
Section: Alterations Of the Olfactory Mucosa Are Linked To Neurodegenerationmentioning
confidence: 99%
“…Alternatively, the culture of olfactory neuronal precursors (ONPs) has emerged as a relatively simpler tool to study different brain disorders, taking advantage of their neuronal lineage and their readily non-invasive isolation [7,8]. For instance, patient-derived ONPs manifest abnormal amyloid components together with tau hyperphosphorylation, which have recently led to the proposal of these cells as a novel diagnostic tool for AD [9][10][11].…”
Section: Introductionmentioning
confidence: 99%